2017
DOI: 10.1089/apc.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to HIV Testing Among Zambian Female Sex Workers in Three Transit Hubs

Abstract: Zambia has a generalized HIV epidemic, and HIV is concentrated along transit routes. Female sex workers (FSWs) are disproportionately affected by the epidemic. HIV testing is the crucial first step for engagement in HIV care and HIV prevention activities. However, to date little work has been done with FSWs in Zambia, and little is known about barriers and facilitators to HIV testing in this population. FSW peer educators were recruited through existing sex worker organizations for participation in a trial rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 28 publications
7
81
0
Order By: Relevance
“…Eleven articles reported that time and transport costs hampered access to healthcare [24, 31, 34, 36, 37, 41, 43, 47, 4952]. Time restraints impeded testing in China [31, 41], India [48], Thailand [43], Vietnam [50], Uganda [51], Zambia [49], Ethiopia [47] and several other African countries (Kenya, Zimbabwe, Uganda and South Africa) [52].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles reported that time and transport costs hampered access to healthcare [24, 31, 34, 36, 37, 41, 43, 47, 4952]. Time restraints impeded testing in China [31, 41], India [48], Thailand [43], Vietnam [50], Uganda [51], Zambia [49], Ethiopia [47] and several other African countries (Kenya, Zimbabwe, Uganda and South Africa) [52].…”
Section: Resultsmentioning
confidence: 99%
“…Both assisted and unassisted modalities are used for HIVST and participants are free to choose the option of their interest [32,33]. Self-testing is thought to be effective service delivery modality for FSWs, particularly to mitigate structural barriers which hinder them from accessing health services in the facility setting [34].…”
Section: Introductionmentioning
confidence: 99%
“…As observed in other settings, our analysis shows that peer-escorted referrals increased confidence and encouraged some FSWs to accept linkage to care (17). These findings underscore the need for expanded coverage of peer-based prevention interventions and comprehensive HIV services for FSWs (1820). Shortcomings of a few peer educators and home-based care providers in handling clients’ information need to be addressed to increase their acceptability in facilitating linkage to care.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, FSWs highlighted that stigma and discrimination in the form of verbal harassment and disclosure of HIV status within the healthcare setting were significant barriers to their linkage to HIV care, which is likely because of their sex work practices and HIV status combined. Interventions focused on health service providers to reduce stigma and discrimination, such as sex work sensitisation training and participatory dialogue, are urgently needed as they have the potential to increase linkage to HIV care among FSWs, a finding that has been highlighted in other studies (20, 25). There is also a need for community sensitisation that highlight the importance of support systems for people living with HIV, to enhance acceptance of those who are diagnosed with HIV (26).…”
Section: Discussionmentioning
confidence: 99%